Essential Oils as a Potential Treatment Option for Pediculosis - Candy, Kerdalidec; Akhoundi, Mohammad; Andriantsoanirina, Valérie; Durand, Rémy; Bruel, Christiane; Izri, Arezki (Planta Medica, 2020)
Pediculosis is a prevalent ectoparasite infestation caused by lice. The head louse (Pediculus humanus capitis) and body louse (Pediculus humanus humanus) are obligatory parasites whose only known hosts are humans. Pediculosis is probably the most common ectoparasitic infestation, affecting up to 80% of the population in several countries, and particularly prevalent in the infant population worldwide. Several treatment options, including shampoos and creams containing insecticides, have been introduced for the treatment of pediculosis. Recently, the use of synthetic chemicals to control human lice has raised concerns pertaining to human health and the environment. Therefore, increasing efforts have been undertaken to develop effective pediculicides with low environmental toxicity and minimal environmental residual activity. In this study, we focus on the essential oils derived from 22 plant genera, their constituents, and the major factors that play important roles in the effectiveness of these oils in the treatment of pediculosis. Furthermore, we discuss the advantages and limitations of the mentioned essential oils, and ultimately suggest those demonstrating the most effective in vitro pediculicidal activities. The genera such as Aloysia, Cinnamomum, Eucalyptus, Eugenia, Lavandula, Melaleuca, Mentha, Myrcianthes, Origanum, Pimpinella, and Thymus appear to be more efficient against lice. These genera are rich in anethole, 1,8-cineole, cinnamaldehyde, p-cymene, eugenol, linalool, limonene, pulegone, terpinen-4-ol, and thymol compounds.
Keywords: pediculosis; Pediculidae; pthiridae; Pediculus humanus capitis; Pediculus humanus humanus; Pthirus pubis; treatment; eco-friendly pediculicides